2023
DOI: 10.1002/epi4.12749
|View full text |Cite
|
Sign up to set email alerts
|

FKBP5 blockade may provide a new horizon for the treatment of stress‐associated disorders: An in‐silico study

Abstract: Objective We searched for, from the FDA (Food and Drug Administration‐USA)‐approved drugs, inhibitors of FKBP5 with tolerable adverse effect profiles (eg, mild headache, sedation, etc.) and with the ability to cross the blood brain barrier (BBB), using bio‐informatics tools (in‐silico). This may pave the road for designing clinical trials of such drugs in patients with functional seizures (FS) and other stress‐associated disorders. Methods Several databases were used to find all the approved drugs that potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Ponatinib is used to treat chronic myeloid leukemia. In an in-silico study, ponatinib was suggested for the treatment of functional seizures 86 , and it also reduced seizure severity in a kainate-induced status epilepticus rat model 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Ponatinib is used to treat chronic myeloid leukemia. In an in-silico study, ponatinib was suggested for the treatment of functional seizures 86 , and it also reduced seizure severity in a kainate-induced status epilepticus rat model 87 .…”
Section: Discussionmentioning
confidence: 99%
“…The drugs discussed in this section are the most promising drugs that can inhibit the FKBP51 protein based on our previous in-silico study. In a previous study, multiple databases were screened, and those therapeutics that can cross the blood-brain barrier (BBB) and have capable pharmacologic and bioinformatic features for interacting with and inhibiting the FKBP5 gene were reported (43). In addition, the effects of different drugs on FKBP51 are listed in Table 3.…”
Section: Drugs Associated With Fkbpmentioning
confidence: 99%
“…Recently, an association between mutations of FKBP5 and functional seizures, another stress-induced disease whose biological aspects are not well known, has been found (41,42). Moreover, in another study, potential drugs for targeting the FKBP51 protein have been investigated and reported (43) because the inhibition of FKBP51 can promote the regulation of the HPA axis in stress-induced disorders (41,43). In this study, we attempted to explain the role of FKBP5 in the human body, especially in the HPA axis and stress-induced disorders, the effects of the most important genetic mutations of this gene in stress-induced disorders, and the potential therapeutic effects affecting FKBP51.…”
Section: Introductionmentioning
confidence: 99%